What drives diversification of national food supplies? A cross-country analysis - Choudhury, Samira; Headey, Derek D. (Elsevier, 2017)
Little previous research has explored what drives the diversification of national food supplies (DFS) across countries and regions. We construct and analyse a cross-country dataset linking a simple DFS indicator - the share of calories supplied by nonstaple foods - with structural transformation and agroecological indicators. Panel econometric models show that several indicators of structural transformation (economic growth, urbanization and demographic change) are strong predictors of diversification within countries, yet time-invariant agroecological factors are also significantly associated with diversification, which appears to explain why some countries have exceptionally low or high DFS relative to their level of economic development. We discuss the implications of these findings for food and nutrition strategies.